Evaluating the Benefits of a Family Support Program on the Health and Well-Being of Aging Family Caregivers of Adults with Intellectual and Developmental Disabilities. Issue 3 (3rd April 2023) - Milberger, Sharon; Marsack-Topolewski, Christina; Janks, Elizabeth; Anderson, Nia; Bray, Michael; Samuel, Preethy S.
ABSTRACT: Providing care to a family member with intellectual and developmental disabilities (I/DD) takes a toll on the health of the caregiver and the family, especially as they age. Research shows that peer mediated family support programs can improve caregiver health and well-being. To date, most family support programs have focused on family caregivers of children and youth with I/DD. The purpose of this study was to examine the benefits of participating in the Michigan Older Caregivers of Emerging Adults with Autism and Neurodevelopmental Disabilities (MI-OCEAN) family support program grounded in the Family Quality of Life (FQOL) framework. Specifically, we examined the effect of participation on health care utilization, caregiver well-being, and perceptions of global FQOL for older caregivers of adults with I/DD. Quantitative analysis of data gathered from 82 caregivers (age 50 and older) indicated that study participation was associated with increased use of Medicaid and improved caregiver well-being (reduced burden, stress, depression; increased health satisfaction and FQOL). Future research is needed to examine the long-term impact of the family support programs in improving the health and well-being of older caregivers of adults with I/DD.